Qualitative Analysis Of Medical Record And Health Information Officers’ Experiences In Using Electronic Medical Records (EMR) Applications Based On The Delone And Mclean Model At Rsud Wangaya Denpasar City - Gede Angga Arviana Putra; I Made Sudarma Adiputra; I Gusti Agung Ngurah Putra Pradnyantara (International Journal of Health Engineering and Technology, 2026)
The development of information technology in the healthcare sector has encouraged healthcare facilities to implement Electronic Medical Records (EMR) systems to improve service efficiency and patient data management. Wangaya Regional General Hospital in Denpasar has implemented EMR in accordance with the Indonesian Ministry of Health Regulation Number 24 of 2022. However, several challenges are still experienced by system users. This study aims to analyze the experiences of Medical Record and Health Information Officers (PMIK) in using the EMR application based on the DeLone and McLean Information System Success Model, which includes system quality, information quality, and service quality. This research employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews with seven PMIK officers at Wangaya Regional General Hospital. The results indicate that the system quality of EMR is considered relatively easy to use and helpful in supporting daily work activities. However, several obstacles were identified, such as occasional system errors, suboptimal diagnosis code searching, and slower system access when the network is unstable. The information quality is considered sufficiently complete and supportive of healthcare services, although there are occasional cases of duplicate medical record numbers or BPJS numbers and delays in data access under certain conditions. Meanwhile, service quality is perceived as fairly good as the system improves service efficiency and facilitates coordination between units, although training programs have not been evenly distributed and the response to technical issues still needs improvement. Overall, the implementation of EMR at Wangaya Hospital has provided benefits in supporting healthcare services; however, further system development and service support are required to optimize its utilization.